Three-dimensional reconstruction imaging by C-arm computed tomography accurately visualizes in-stent neointimal formation in patients with stent-assisted coil embolization - Kotsugi, Masashi; Nakagawa, Ichiro; Konishi, Kengo; Tanaka, Haku; Sasaki, Hiromitsu; Furuta, Takanori; Okamoto, Ai; Nakase, Kenta; Maeoka, Ryosuke; Yokoyama, Shohei; Yamada, Shuichi; Nakase, Hiroyuki (Frontiers in Neurology, 2023)
Background Stent apposition to the vessel wall and in-stent neointimal formation after stent-assisted coil embolization for intracranial aneurysm are important factors associated with postoperative thromboembolic complications. No assessment methods have been established to depict 3-dimensional (3D) all-round in-stent neointimal formation. Objective To demonstrate the superiority of Dyna-3D imaging assessment as a modality for all-round ISNF in comparison with conventional two-dimensional digital subtraction angiography (2D-DSA). Methods Consecutive patients who underwent braided stent-assisted coil embolization for unruptured aneurysm between November 2016 and September 2021 were enrolled. Radiological assessments for stent apposition to the parent vessel after stent deployment and in-stent neointimal formation after 3 months were obtained. Dyna-3D was reconstructed by overlapping a plain image showing stent struts with a rotational DSA image showing the vessel lumen. Reconstructed Dyna-3D images can be rotated to any angle on the screen to evaluate to stent apposition around the vessel and in-stent neointimal formation in 3D, for comparison with 2D-DSA evaluations. Results Among the 73 patients enrolled, 70 patients (96%) showed complete stent wall apposition on Dyna-3D. Higher intra-rater agreement was confirmed on assessment of in-stent neointimal formation with Dyna-3D (Cohen’s κ = 0.811) than with conventional 2D-DSA (Cohen’s κ = 0.517). in-stent neointimal formation could not be confirmed on conventional imaging in 9 cases (16%) and on Dyna-3D in 2 cases (3%). The number of in-stent neointimal formations rated as stent wire completely outside the endothelial line was significantly higher with Dyna-3D than with 2D-DSA (p = 0.0001). Conclusion All-round 3D evaluation by Dyna-3D imaging appears useful for confirming in-stent neointimal formation after braided stent deployment in patients after stent-assisted coil embolization.